2017
DOI: 10.1016/j.exger.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sensorimotor peripheral nerve function and indicators of cardiovascular autonomic function in older adults from the Health, Aging and Body Composition Study

Abstract: Background Age-related peripheral nervous system (PNS) impairments are highly prevalent in older adults. Although sensorimotor and cardiovascular autonomic function have been shown to be related in persons with diabetes, the nature of the relationship in general community-dwelling older adult populations is unknown. Methods Health, Aging and Body Composition participants (n=2,399, age=76.5±2.9 years, 52% women, 38% black) underwent peripheral nerve testing at the 2000/01 clinic visit. Nerve conduction amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Additionally, poor sensorimotor peripheral nerve function is related to slower endurance walking and greater slowing longitudinally [28]. A recent study indicated that there is an association with indicators of cardiovascular autonomic function and sensorimotor peripheral nerve impairments [29]. The current study adds to these findings in demonstrating a greater risk of swallowing difficulties in older persons with sensorimotor peripheral nerve impairments.…”
Section: Discussionsupporting
confidence: 50%
“…Additionally, poor sensorimotor peripheral nerve function is related to slower endurance walking and greater slowing longitudinally [28]. A recent study indicated that there is an association with indicators of cardiovascular autonomic function and sensorimotor peripheral nerve impairments [29]. The current study adds to these findings in demonstrating a greater risk of swallowing difficulties in older persons with sensorimotor peripheral nerve impairments.…”
Section: Discussionsupporting
confidence: 50%
“…For example, parallel involvement of peripheral neuropathy and DCAN may principally affect the more vulnerable large nerve fibers ( 34 ). Parallel development of DCAN and peripheral neuropathy is thought to involve vulnerable large nerve fibers, with recent evidence pointing to an association between parasympathetic nervous system impairment and reduced peroneal motor nerve CV ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…OH has been associated with poor peripheral motor nerve function in older adults. 35 It has also been associated with greater white matter hyperintensities on magnetic resonance imaging, which is thought to reflect cerebral small vessel disease, in late life depression. 36 A number of cross-sectional and longitudinal studies have linked these brain changes to mobility decline.…”
Section: Discussionmentioning
confidence: 99%